Recent Practices of People's Participation in Different Avenues of Rural Local Government - Tanjil Ahmed; Azizur Rahman; Tamanna Akter (PCD Journal, 2022)
People's participation in various avenues of local administration is crucial for strengthening decentralisation in Bangladesh, despite the fact that such participation faces significant. The main purpose of this research is to explore the most current trends in people's participation in different avenues of local government. This research also examines the realities and challenges involved in strengthening decentralisation in Bangladesh. Using a quantitative methodology, this research found that different avenues of people's participation in Union Parishads has fostered successful decentralisation since these avenues certify independent participation and enable them to share their opinions and influence decision-making processes. Since decentralisation facilitates the transfer of power from the central to the local level, people's participation is functional within Union Parishads. Moreover, this research demonstrates that most rural people are severely challenged in participating in the different avenues of Union Parishads due to political complexity, institutional corruption, poor education, and general unawareness. The authors therefore suggest that, by implementing public awareness programmes, ensuring the maximum autonomy of local government units, and confirming the accountability and transparency of service providers, people's participation can strengthen the decentralisation of rural local government in Bangladesh.